A Novel Polysaccharide Isolated From Fresh Longan (Dimocarpus longan Lour.) Activates Macrophage via TLR2/4-Mediated PI3/AKT and MyD88/TRAF6 Pathways - Haibo Lan; Haibo Lan; Haibo Lan; Wu Li; Jucai Xu; Yuzhe Yang; Zhaolun Tan; Ruili Yang (Frontiers Media S.A., 2021)
A novel immunomodulatory polysaccharide (LP4) with a molecular weight 6.31 × 104 g/mol was purified from fresh longan pulp. It was composed of mannose, glucose, glucuronic acid, galactose, xylose, arabinose, galacturonic acid, fucose, and rhamnose in a molar percentage of 36:31:10:7:4:4:3:2:2, and mainly linked by (1→6)-β-Man, (1→4)-β-Glc and (1→6)-α-Glc. LP4 can obviously enhance the phagocytosis of macrophages and promote the proliferation of lymphocytes. After treating macrophages with LP4 (12.5-50 μg/ml), the production of IL-1β and TNF-α was significantly increased. These increases of cytokines were suppressed when the TLR2/TLR4 receptors were inhibited by anti-TLR2 and/or anti-TLR4 antibodies. Moreover, the mRNA expression of INOS, AKT, PI3K, TRAF6 and MyD88 was significantly suppressed by TLR2/TLR4 antibodies. These results indicated that LP4 induced macrophage activation mainly via the TLR2 and TLR4-induced PI3K/AKT and MyD88/TRAF6 pathways.